National survey of clinical pharmacy services - Tenni, P.; Hughes, Jeff (Society of Pharmacy Practice and Research, 2016)
Objective: To determine the extent of provision of clinical pharmacy services in Australian hospitals and documentation relating to these. Further to evaluate the suitability of the information collected to demonstrate the benefits of these services. Method: The National Survey of Clinical Pharmacy Services (NSCPS) was undertaken during October 1995. A questionnaire was sent to 309 public and private hospitals which sought information on a range of clinical pharmacy services in major areas of clinical pharmacy practice. The information requested concerned the frequency of provision of the service and any specific information thought to demonstrate the benefit(s) of the service. Following review of responses to the questionnaire pharmacy departments were identified for follow-up to obtain more detailed information on the type and extent of documentation available. This information was then used to make recommendations concerning the applicability of the available information within each clinical service for collation and further study. Results: The prevalence of clinical pharmacy services within four broad areas of clinical pharmacy practice based on data from 111 respondents was: drug therapy monitoring, 96%; provision of drug information and education, 98%; drug utilisation reviews and evaluations and the promulgation of therapeutic guidelines and protocols, 96%; and community liaison services, 78%. The type and extent of documentation relating to each clinical pharmacy service varied amongst hospitals. Conclusion: The survey demonstrated that clinical pharmacy services arc common within Australian hospitals. Furthermore, documentation relating to these services was widespread. The nature of the documentation, however varied amongst institutions. This variation limits the usefulness of the information for nation-wide collation and further study. There is a need to standardise the type of information collected for each clinical pharmacy service in order to allow collation of information from multiple centres.